Spark plasma sintering of aluminum nitride - Tan, Mui Ting. (2008)
As the speed and power requirements in electronics increase, the heat dissipation problems and the signal delay caused by the capacitive effect of the dielectric material become important issues. Thermal management has indeed become a critical factor in the electronics industry. This project aims to evaluate the effect of various sintering parameters on synthesis through spark plasma sintering (SPS).